Mullerian Inhibiting Substance Suppresses Proliferation and Induces Apoptosis and Autophagy in Endometriosis Cells In Vitro - Borahay, Mostafa A. (Hindawi Publishing Corporation, 2013)

(untitled)
Objective. To determine the effects of Mullerian inhibiting substance (MIS) treatment on endometriosis cells through study of apoptosis and autophagy. Design. Experimental in vitro study. Setting. University research laboratory. Cell Line. CRL-7566 endometriosis cell line. This line was established from a benign ovarian cyst taken from a patient with endometriosis. Interventions. In vitro treatment with MIS. Main Outcome Measures. The main outcome measures were cellular viability, proliferation, cell-cycle arrest, and induction of apoptosis and autophagy in endometriotic cells. Results. MIS treatment inhibited proliferation of endometriosis cells and induced apoptosis, as indicated by Annexin V staining, and induced caspase-9 cleavage and cell-cycle arrest, as evidenced by increased expression of p27 CDK-inhibitor. MIS treatment also induced autophagy in endometriosis cells as demonstrated by a significant increase in LC3-II induction, a hallmark of autophagy. Conclusions. MIS inhibits cell growth and induces autophagy, as well as apoptosis, in ectopic endometrial cell lines. Our results suggest that MIS may have a potential as a novel approach for medical treatment of endometriosis. Further studies may be needed to test the efficacy of MIS treatment in animal models and to develop MIS treatment specifically targeted to the endometriosis.